Design, Synthesis and Molecular Docking of Thiophene Derived Benzodiazepines as Anticancer Agents - Ishwar Bhat, K.; Cyriac, Chinchumol; Vijaybhasker, K.V. (Asian Journal of Chemistry, 2022)
A new series of 1,4-benzodiazepines were synthesized based on the results of molecular docking. The designed compounds were docked in the groove of binding sites present in human estrogen receptor 2IOK and EGFR receptor 4WKQ. The physico-chemical properties, Lipinski’s Rule of 5 and ADMET properties were calculated for the compounds by using the Qikprop application in Schrödinger software and on the basis of molecular docking fifteen compounds were designed. Because of poor yield in some cases, only ten compounds have been synthesized. All the newly synthesized compounds were established based on IR, 1H NMR and mass spectral data. The new compounds were screened for in vitro anticancer activity. Among all the compounds, compound BZ4 had the highest binding energies and showed the potential cytotoxicity when screened for anticancer activity by MTT assay.